The feet of the measles virus polymerase bind the viral nucleocapsid protein at a single site - Yegambaram, Kavestri (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Measles virus has a single-stranded RNA genome that is organized into a helical complex by the viral N protein. The resulting structure is termed the nucleocapsid and is traversed by the viral polymerase during RNA synthesis. The P protein, the noncatalytic subunit of the polymerase, provides the “legs and feet” that allow the polymerase to walk along its protein-RNA template. The polymerase feet are very simple three-helix bundles, only 50 amino acids in size. Previously, we have shown that these feet grasp the viral N protein during movement by attaching to a short sequence (amino acids 487–503) within the disordered and surface-exposed tail of N, causing it to fold into a helix. The result is a weak-affinity complex with a short lifetime, which would allow the polymerase to take rapid steps forward. The structure of the complex was determined using X-ray crystallography. This simple model of binding was challenged by a paper in this journal, claiming that a downstream sequence in the tail of N (amino acids 517–525) was also critical for the association. Its presence was reported to enhance the overall affinity of the polymerase feet for N by three orders of magnitude. We have, therefore, examined binding of the polymerase foot domain to amino acids 477–525 of N using quantitative biophysical techniques, and compared the results to our previous binding studies, performed using amino acids 477–505 of N. We find no evidence that the sequence downstream of amino acid 505 influences binding, validating the original single-site binding model.